Manpower needs in construction (foreign labour issues) - Razlina, Mohamed (2015)
The growth of Malaysia's economic makes growing construction industry. However, employment in the construction sector less attractive to local workers. Due to this problem, the provision of foreign workers used to curb the shortage of workers and recruitment of foreign workers is becoming increasingly important to meet the needs of workers in the construction sector. This research is more likely to service the needs of the foreign workers issue. In this research, the cause of foreign workers as well as ways to reduce the use of foreign workers in the construction sector discussed in more depth. Review of literature was conducted and a questionnaire survey was used to obtain the information needed to meet the requirements of this inquiry. The questionnaire was distributed to 61 respondents and 47 respondents are responding with the survey. The distribution was involved registered contractor in Kuantan area where it is involve grade one (1) until seven (7). From the questionnaire survey, the analysis shows that the three (3) most factor of employer hiring foreign labour is Foreign Labour Can Be Easily Bring In, Higher Educational Level, And Low Wages For Construction Jobs. Meanwhile second objective is ways to minimize the reliance of foreign labour, the data analysis shows that three (3) most best ways is Tighten Hiring Rules, National Vocational Training Council (NTVC), and Green Card System. In conclusion, Foreign labour can bring easily in construction industry where their just accept even the offer with low wages and also willing to working long hours make employer more easier in to fully the demand of construction industry. Furthermore, Low wages was offered by employer in construction field, certain few local willing to working in construction industry. With tighten hiring rules in over supply of foreign labour is needed to enforceable by government to avoid the damping of foreign labour. Besides that, National Vocational Training Council (NTVC) was disclosed for young local generation with provided program with skills training for fully the demand construction industry intensive to new or modern technology.